Empowering Adult Learners Through Lifelong Learning Strategies for Enhancing Participation and Skill Development in Non-Formal Education - Robert Ferdinand; Emma John Smith (PT Mutiara Bustan Ilmu, 2025)
This study explores strategies for empowering adult learners through lifelong learning in non-formal education settings, focusing on enhancing participation and skill development. The research employed a qualitative approach, incorporating participatory methods, observations, interviews, and document analysis to understand learner experiences and program effectiveness. Findings reveal that experiential learning, peer collaboration, flexible course structures, mentorship, and problem-based learning significantly contribute to increased engagement, practical skill acquisition, and self-confidence among adult learners. Moreover, aligning learning content with learners’ socio-economic contexts enhances relevance and motivation, while digital tools expand accessibility and participation. Overall, the study demonstrates that learner-centered, contextually relevant lifelong learning initiatives can effectively empower adults, foster autonomy, and promote continuous skill development, with implications for policy and practice in non-formal education.